Non-State actors and their impact on international relation - Dr. Teacher: Yassin Hadi Thajeel. (The college of law and political science journal, 2025)
The tremendous developments in the fields of technology, communications, and information have coincided with a major shift in the policies of major powers, believing that pursuing their interests is more important than the promises of noble ideologies. This is a major reason behind the presence of non-state actors as social or non-governmental economic entities. As a result, states have become unable to play the role of the sole player in international relations, instead relinquishing some of their roles to these actors. If politics allowed for good intentions, non-state actors could have been a support for states and their governments in achieving the security and interests of nations. However, most non-state actors have been contained or utilized by major powers to change the direction and course in their favor, thus gradually causing a shift in the international system's security and international relations towards new directions. This has clearly contributed to increasing the security vulnerability of the nation-state and has added new threats and challenges to these countries.